1999
DOI: 10.1038/5960
|View full text |Cite
|
Sign up to set email alerts
|

Human homologue of the Drosophila melanogaster lats tumour suppressor modulates CDC2 activity

Abstract: We have previously used mosaic flies to screen for tumour suppressors or negative regulators of cell proliferation. The cellular composition of these flies resembles that of cancer patients who are chimaeric individuals carrying a small number of mutated somatic cells. One of the genes we identified is the large tumour suppressor gene, lats (also known as wts), which encodes a putative serine/threonine kinase. Somatic cells mutant for lats undergo extensive proliferation and form large tumours in many tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(219 citation statements)
references
References 28 publications
6
209
1
3
Order By: Relevance
“…In contrast, LATS1/2 kinases, which can also signal downstream of MST1/2 [13,14,83], have been shown to play a role in later stages of mitosis. A decade ago, it was reported that LATS1 can inhibit CDK1 activity in mitosis, thereby influencing G2/M cell cycle progression [25,84]. Analysis of cells overexpressing LATS1 supported a role for LATS1 in mitosis, since LATS1 overexpression resulted in a G2/M cell cycle arrest [84][85][86].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 90%
See 2 more Smart Citations
“…In contrast, LATS1/2 kinases, which can also signal downstream of MST1/2 [13,14,83], have been shown to play a role in later stages of mitosis. A decade ago, it was reported that LATS1 can inhibit CDK1 activity in mitosis, thereby influencing G2/M cell cycle progression [25,84]. Analysis of cells overexpressing LATS1 supported a role for LATS1 in mitosis, since LATS1 overexpression resulted in a G2/M cell cycle arrest [84][85][86].…”
Section: Mammalian Hippo Signalling In the G2/m Phase Of The Cell Cyclementioning
confidence: 90%
“…The authors speculated that Lats might accelerate progression through G2/M, thereby shifting more cells into G1 [59]. In light of the finding that Lats can inhibit CDK1 during mitosis in human cells and flies [25], this interpretation might be correct. However, we currently cannot exclude the other possible interpretation of this finding, namely that loss of Lats function results in a G1 cell cycle arrest.…”
Section: Hippo Signalling In G2/m In Drosophila Melanogastermentioning
confidence: 99%
See 1 more Smart Citation
“…1B). It has been demonstrated that human YAP, Lats1, Mst2, and Mob1 can rescue the phenotypes of their corresponding Drosophila mutants in vivo (Tao et al, 1999;Wu et al, 2003;Huang et al, 2005;Lai et al, 2005), suggesting the functional conservation of these proteins. The core components Mst1/2 are known to be pro-apoptotic kinases that are activated by caspase cleavage under apoptotic stress (Graves et al, 1998).…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…A mammalian homolog of the Drosophila tumorsuppressor protein warts, known as WARTS (or large tumor-suppressor 1 (LATS1)), was identified (Nishiyama et al, 1999;Tao et al, 1999) and found to have functions similar to its activity in Drosophila: mice deficient in WARTS (WTS)/LATS1 develop malignant tumors . WTS encodes a serine-threonine kinase that shares a high degree of sequence homology with members of the myotonic dystrophy protein kinase (DMPK) family, many of which participate in mitotic events.…”
Section: Introductionmentioning
confidence: 99%